The Distribution and biogeography of the cryptic multimammate mice, mastomys natalensis (A. Smith, 1834) and Mastomys coucha (A. Smith, 1836) in southern Africa - M. van der Merwe (University of Pretoria, 2022)
Dissertation (MSc (Zoology))--University of Pretoria, 1997.